Organocatalysis: asymmetric cascade reactions catalysed by chiral secondary amines - Yu, Xinhong; Wang, Wei (Organic & biomolecular chemistry, 2008)
The utilisation of chiral secondary amines as promoters for asymmetric cascade reactions has been subject of intensive research in asymmetric organocatalysis in the past few years. Key developments in this area are highlighted in this review. As shown, these powerful synthetic methodologies serve as efficient approaches to the construction of complex chiral molecular architectures from simple achiral materials in one-pot transformations under mild conditions with high stereocontrol.